Pengaruh kadar air umpan dan rasio C/N pada produksi biogas dari sampah organik pasar - Zuliyana Zuliyana; Sang Kompiang Wirawan; Wiratni Budhijanto; Rochim B Cahyono (Jurnal Rekayasa Proses, 2015)
Nowadays, Indonesia is facing serious problem related to the rapid generation of municipal solid waste (MSW) and dependence on fossil energy. Converting organic content of MSW into biogas through biological process by mean of anaerobic digester is one of promising proposals to solve the MSW problem. In order to optimize biogas production, this research studies the effect of Total Solid (TS) content and ratio of carbon to nitrogen (C/N) within organic fraction of MSW as raw material for biogas production. The organic fraction of MSW consists of vegetables and fruits waste which originated from traditional market.The experiments using various TS concentrations (10%, 15% and 20%) were conducted in batch reactors. The results showed that TS content of MSW raw material had significant effects on the total volume and CH4 concentration of biogas production. High water content in MSW raw material enhanced the hydrolysis of organic fraction as well as avoided the excessive Volatile Fatty Acid (VFA) concentration which posed the risk of inhibition on the anaerobic process. Based on the results, the TS concentration of 10-15% in the organic MSW would offer an optimum yield of biogas production. In order to examine the effect of C/N ratio, the organic MSW was modified using ZA fertilizer (36, 30, 20 and 10 C/N ratios). The C/N ratios of 20-30 produced high amount biogas and CH4 concentration compared to others. The C/N ratio should be maintained at the optimum value to prevent the accumulation of free ammonia which could cause problems in the anaerobic process.Based on the results, the biogas production from organic MSW would yield the optimum biogas amount and CH4 concentration when the TS concentration and C/N ratio were 10-15% and 20-30, respectively. This outcome would give recommendation on the water addition to the raw organic fraction of MSW and C/N modification when converting the organic fraction of MSW to biogas.